2012
DOI: 10.1007/s00586-012-2377-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of upper limb loading on spinal shrinkage during treadmill walking

Abstract: Introduction Everyday activities such as walking may elicit spinal shrinkage in an order of magnitude that has been related to lower back pain. The present study aims to compare the effects of unloaded treadmill walking with walking carrying loads representing everyday shopping tasks. Materials and methods Walking tasks were performed on seven healthy males and motion analysis was used to track four reflective markers at 100 Hz, dividing the spine into three segments. Static data was collected in 5-min interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The study found an evidence of favoring the two-hands carrying to the one-hand carrying in general based on the investigated physiological responses in the form of lower cardiac cost and lower %MVC and subjective response in the form of lower discomfort rating. This finding is in support of other studies, which investigated different responses such as trunk kinematics [ 3 , 6 , 7 ], trunk loading [ 8 , 15 ], and gait analysis [ 4 , 10 , 11 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The study found an evidence of favoring the two-hands carrying to the one-hand carrying in general based on the investigated physiological responses in the form of lower cardiac cost and lower %MVC and subjective response in the form of lower discomfort rating. This finding is in support of other studies, which investigated different responses such as trunk kinematics [ 3 , 6 , 7 ], trunk loading [ 8 , 15 ], and gait analysis [ 4 , 10 , 11 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Participants were asked to walk steadily at their normal walking speed and avoid any sudden or aggressive moves that might result in sudden loading of the spine [ 3 , 37 – 39 ]. After 90 seconds of walking, PPPs and 15-second sEMG muscular activities were recorded one time every minute for three minutes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations